Pemanfaatan Ekskreta Ayam Layer Terfermentasi terhadap Kandungan Nutrisi, Panjang dan Berat Maggot Black Soldier Fly (BSF) - Fitriana Heni Tiali Susanti; Rayhan Rafif Maheswara; Tulus Setyobudi; Indria Nur Khasanah; Nova Fahrizal Hidayat (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2025)
Utilization of fermented layer chicken excreta as a feed medium for Black Soldier Fly (BSF) maggots is a sustainable solution for organic waste management. Chicken excreta contains 13-32% crude protein, but has disadvantages such as unbalanced nutrient composition and unpleasant odor. Fermentation of chicken excreta can improve maggot production performance by reducing pathogens, odor, and facilitating digestion. The growth medium of 50% excreta + 50% tofu dregs produced the highest PK, which was 34.34%. The lowest SK and LK were obtained from the growth medium of 50% excreta + 50% tofu dregs and 25% excreta + 75% tofu dregs. Based on physical conditions, the longest and heaviest maggot sizes were obtained from the growth medium of 50% excreta + 50% bran + 5 ml EM4. Meanwhile, the shortest maggots were obtained from the growth medium of 75% coconut dregs + 25% excreta and the lightest maggots were obtained from the growth medium of 100% excreta.